2021
DOI: 10.1093/cid/ciab737
|View full text |Cite
|
Sign up to set email alerts
|

External Validation and Comparison of Clostridioides difficile Severity Scoring Systems

Abstract: Background Many models have been developed to predict severe outcomes from Clostridioides difficile infection. These models are usually developed at a single institution and largely are not externally validated. This aim of this study was to validate previously published risk scores in a multicenter cohort of patients with CDI. Methods Retrospective study on four separate inpatient cohorts with CDI from three distinct sites: … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
13
1

Year Published

2022
2022
2023
2023

Publication Types

Select...
4
2

Relationship

3
3

Authors

Journals

citations
Cited by 10 publications
(14 citation statements)
references
References 43 publications
0
13
1
Order By: Relevance
“…Furthermore, there is variation in the genome, growth rate, sporulation, germination, and toxin production in different isolates of a strain (34)(35)(36)(37). This variation may help explain why severe CDI prediction tools often miss identifying many patients with CDI that will develop severe disease (3,23,38,39). Therefore, it is necessary to gain a full understanding of all factors contributing to disease variation to improve our ability to predict severity.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Furthermore, there is variation in the genome, growth rate, sporulation, germination, and toxin production in different isolates of a strain (34)(35)(36)(37). This variation may help explain why severe CDI prediction tools often miss identifying many patients with CDI that will develop severe disease (3,23,38,39). Therefore, it is necessary to gain a full understanding of all factors contributing to disease variation to improve our ability to predict severity.…”
Section: Discussionmentioning
confidence: 99%
“…Since these measures are CDI outcomes, they have limited ability to predict risk of severe CDI when the infection is first detected. Schemes have been developed to score a patient’s risk for severe CDI outcomes based on clinical factors but have not been robust for broad application (3). Thus, we have limited ability to prevent patients from developing severe CDI.…”
Section: Introductionmentioning
confidence: 99%
“…While several CDI severity and complication scoring systems have been developed previously, they generally were developed from single centers and were not externally validated [5][6][7][8][9][10][11][12][13][14]. Our group recently published the largest external validation of published CDI severity scoring systems and found that all models yielded AUC scores below 70% suggesting that current models are not generalizable and cannot reliably predict severe complications from CDI [15].…”
Section: Discussionmentioning
confidence: 99%
“…We conducted a multi-center retrospective longitudinal cohort study at four geographically and temporally distinct cohorts, including the University of Michigan (2010)(2011)(2012)(2015)(2016), University of Wisconsin (2014Wisconsin ( -2015, and University of Chicago (2013)(2014)(2015), as previously described by Perry et al [15]. Adult subjects ≥18 years who were diagnosed with CDI were included in our analysis.…”
Section: Patient Cohortsmentioning
confidence: 99%
See 1 more Smart Citation